2014
DOI: 10.1177/0486613414537986
|View full text |Cite
|
Sign up to set email alerts
|

Labor Process and the Social Structure of Accumulation in China

Abstract: Inspired by the interplay between social structure of accumulation theory and labor process theory, this paper is to specify the particular mechanism that labor institutions take in accomplishing China’s rapid capital accumulation in the reform era. The paper starts by proposing a framework to understand the relation among overtime work, labor process, and the wage gap and presents the puzzling contradiction between low wages and the need to sustain the reproduction of labor power for Chinese workers. The pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 11 publications
0
17
0
1
Order By: Relevance
“…We measure the wage pressure with the ratioof a living wage standard to the average wage. In China, the average wage does not meet the living wage level that is sufficient to sustain the reproduction of labor power, which has been a long-lasting problem (LI and QI, 2014). In many private firms, workers have to work overtime to earn overtime payments and increase their total income, which allows managers to discipline their employees through allocating overtime opportunities among workers.…”
Section: A Time Series Analysis Of the Factors That Affect Profitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…We measure the wage pressure with the ratioof a living wage standard to the average wage. In China, the average wage does not meet the living wage level that is sufficient to sustain the reproduction of labor power, which has been a long-lasting problem (LI and QI, 2014). In many private firms, workers have to work overtime to earn overtime payments and increase their total income, which allows managers to discipline their employees through allocating overtime opportunities among workers.…”
Section: A Time Series Analysis Of the Factors That Affect Profitabilitymentioning
confidence: 99%
“…Regarding wages, the economy witnessed fast real wage growth. Nevertheless, this increase does not imply that workers afford decent living conditions (LI and QI, 2014). Workers still have to rely on overtime work to meet the living wage standard and cover the wage gap.…”
Section: Undermined Conditions For the Profitability And The "New Normentioning
confidence: 99%
“…20 The share of migrant workers in total urban employment was increasing in the 1990s and 2000s; by contrast, this proportion became stable after 2008, and slightly declined after 2010. Regarding wages, the economy witnessed fast real wage growth; however, fast real wage growth does not imply that workers afford decent living conditions (Li & Qi 2014;Xu et al 2015). Insufficient wages for decent living conditions imply that it might be impossible to reverse the rising trend of the real wage.…”
Section: Letmentioning
confidence: 99%
“…By not paying a living wage, private enterprises are indirectly subsidized. 13 Li et al (2013) and Li and Qi (2014) showed that the profits of private enterprises would become negative if they were required to pay wages according to China’s Labor Law. Besides, most SOE employees have access to social security, while only a few private enterprise employees have access to it.…”
Section: How Soes Can Promote Economic Growthmentioning
confidence: 99%